Freezing tendency towards 4-coordinated amorphous networks causes an increase in the heat capacity of supercooled Stillinger-Weber silicon - Apte, Pankaj A.; Pingua, Nandlal; Gautam, Arvind Kumar; Kumar, Uday; Willow, Soohaeng Yoo; Zeng, Xiao Cheng; Kulkarni, B. D. (RSC Advances, 2015)
Supercooled liquid silicon (Si), modeled by the Stillinger-Weber (SW) potential, has been shown to undergo transition to low density amorphous phases at 1060 K in previous studies. Furthermore, the constant pressure heat capacity C-p has been found to exhibit a large increase as the liquid is cooled to 1060 K. In this work, we examine the nature of the equilibrium and the relaxation process of supercooled SW Si in the temperature range of 1060 K to 1070 K at zero pressure. We find that the relaxation of the supercooled liquid leads to a sharp irreversible decrease in the fluctuation of the two body energy of the largest connected network of 4-coordinated particles. Such a process implies a tightening of the bonds (i.e. freezing or jamming) of the network, and is accompanied by a sharp increase in the fraction of the 4-coordinated particles in the system. We find that the jamming (or freezing) process shows a sudden acceleration across a dynamical instability point that occurs at a unique potential energy state of the network. Further, we find that the occurrence of the dynamical instability is associated with the appearance of a straight line region in the cumulative potential energy distributions with a configurational temperature close to 1060 K. We conclude that the supercooled liquid state must be regarded as a constrained equilibrium state, since the accessible microstates are constrained by the inherent tendency of the system to approach the dynamical instability point. Thus all properties of supercooled liquid SW-Si, including the rise in C-p at 1060 K, can be attributed to the freezing tendency of the 4-coordinated particle network.